Gastric sleeve compared to Roux-y gastric By-pass in the treatment of severe obesity in the state of Santa Catarina between 2015 and 2021 (Research, Society and Development, 2023)
Obesity is excess body fat, which is associated with the risk of developing chronic diseases, such as type II diabetes mellitus (DMII), cardiovascular disease, dyslipidemia, among others. In Brazil, 50% of the adult population and 15% of children are overweight. Bariatric surgery is an effective treatment for severe obesity (BMI>40), generating marked weight loss that is sustained over the long term. The two most performed bariatric surgeries in the world are the Roux-en-Y gastric bypass (BP) and the Vertical Gastrectomy or Gastric Sleeve (SV). In Brazil, BP is still the most common surgery. Between 2013 and 2018, 1,629 SV and 43,211 BP were performed. The objective of the study is to compare the use of VS with BP in the treatment of severe obesity in SC between 2015 and 2021. This is an ecological study, for which data on procedures approved by the SUS in SC were collected from the System of Hospital Information (SIH-SUS) found in DATASUS. 1850 procedures were performed in SC, of which 113 were performed by SV and 1737 by LP. It is concluded, when evaluating the linear regression rates of the trend of the use of BP and SV in SC between 2015 and 2021, the presence of reduction with the use of BP and of stability with the use of SV, as well as a behavior of stability in relation to linear regression rates of mean length of hospital stay for VS and BP in Santa Catarina.